A unique combination of natural fatty acids from Hermetia illucens fly larvae fat effectively combats virulence factors and biofilms of MDR hypervirulent mucoviscus Klebsiella pneumoniae strains by increasing Lewis acid–base/van der Waals interactions in bacterial wall membranes - Mohamed, Heakal; Marusich, Elena; Divashuk, Mikhail; Leonov, Sergey (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionHypervirulent Klebsiella pneumoniae (hvKp) and carbapenem-resistant K. pneumoniae (CR-Kp) are rapidly emerging as opportunistic pathogens that have a global impact leading to a significant increase in mortality rates among clinical patients. Anti-virulence strategies that target bacterial behavior, such as adhesion and biofilm formation, have been proposed as alternatives to biocidal antibiotic treatments to reduce the rapid emergence of bacterial resistance. The main objective of this study was to examine the efficacy of fatty acid-enriched extract (AWME3) derived from the fat of Black Soldier Fly larvae (Hermetia illucens) in fighting against biofilms of multi-drug resistant (MDR) and highly virulent Klebsiella pneumoniae (hvKp) pathogens. Additionally, the study also aimed to investigate the potential mechanisms underlying this effect.MethodsCrystal violet (CV) and ethidium bromide (EtBr) assays show how AWME3 affects the formation of mixed and mature biofilms by the KP ATCC BAA-2473, KPi1627, and KPM9 strains. AWME3 has shown exceptional efficacy in combating the hypermucoviscosity (HMV) virulent factors of KPi1627 and KPM9 strains when tested using the string assay. The rudimentary motility of MDR KPM9 and KP ATCC BAA-2473 strains was detected through swimming, swarming, and twitching assays. The cell wall membrane disturbances induced by AWME3 were detected by light and scanning electron microscopy and further validated by an increase in the bacterial cell wall permeability and Lewis acid-base/van der Waals characteristics of K. pneumoniae strains tested by MATS (microbial adhesion to solvents) method.ResultsAfter being exposed to 0.5 MIC (0.125 mg/ml) of AWME3, a significant reduction in the rudimentary motility of MDR KPM9 and KP ATCC BAA-2473 strains, whereas the treated bacterial strains exhibited motility between 4.23 ± 0.25 and 4.47 ± 0.25 mm, while the non-treated control groups showed significantly higher motility ranging from 8.5 ± 0.5 to 10.5 ± 0.5 mm.ConclusionIn conclusion, this study demonstrates the exceptional capability of the natural AWME3 extract enriched with a unique combination of fatty acids to effectively eliminate the biofilms formed by the highly drug-resistant and highly virulent K. pneumoniae (hvKp) pathogens. Our results highlight the opportunity to control and minimize the rapid emergence of bacterial resistance through the treatment using AWME3 of biofilm-associated infections caused by hvKp and CRKp pathogens.